Cerita 5 Sahabat: Dongeng Bertema Pancasila - Adityara, Sarah; Candrasari , M.C Wara (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
The development of the times and the ease with which information is obtained, makes Indonesian people easily accept new ideologies whose application is not in accordance with the values of Pancasila. Lack of understanding of the values of Pancasila results in children discriminating in making friends, being arbitrary and selfish so that there are still many cases of bullying in elementary school students in Indonesia. The need to cultivate Pancasila through media that is easy to understand and does not suppress such as Picture Book. The creation of this work of art uses research methodology research, namely Research-Ied Practice where practice is based on research. The artist conducts research in the field first by looking for literature sources on the internet and books on the topic of Pancasila, which are then applied in practice in the process of creating Fine Art works in the form of picture books.The process of making a picture book is done with digital media, namely Drawing Tablet Ipad with Procreate and Adobe Photoshop applications, with a chibi illustration style and printed on art paper into a picture book consisting of 5 series. There are 5 characters who become the main role in each series, telling the daily life of children in which the values of Pancasila are implied.